Factors Associated with Contraceptive Use among Early Married Couples in Aikmel Subdistrict, East Lombok District - Hery Aryanti; Luh Seri Ani; I Nyoman Mangku Karmaya (Public Health and Preventive Medicine Archive, 2014)
Background and purpose: Early marriage considered as a major issue in Indonesia including West Nusa Tenggara Province with a prevalence of 23.9%. This results in the increasing number of total fertility rate (TFR) as many as 2.8 children. This is higher than the national TFR (2.36). An effective implementation of family planning program can decrease TFR. Until currently very limited study have identified factors associated to the use of contraceptive methods among early marriage couple in Aikmel Subdistrict East Lombok. Method: This is a cross-sectional quantitative study involving 84 early marriage women in Aikmel Subdistrict East Lombok. Samples were selected using convenience method and were interviewed to obtain data related to characteristic, contraceptive method history, knowledge, information from health provider and support from their husband. Data were analysed using univariate and bivariate (chi square test). Results: The majority of respondent’s first time marriage were at aged ≥17 year (64.3%). Most of the respondents have low education level (66.7%) and do not work (57.1%), have low level of knowledge (92,9%), lack of information from health provider (91.7%) and lack of support from husband (51.2%). Husband’s support was found to be the most significant factor associated to contraceptive use among early marriage women (p<0,001). Other factors including age at first marriage, education level, employment, level of knowledge and information from health providers were not statistically associated to contraceptive use. Conclusion: Support from husband is the most significant factor associated to contraceptive use among early marriage women in Aikmel Subdistrict East Lombok.